Pengaruh Model Two Stay Two Stray Melalui Diagram Fishbone Terhadap Keterampilan Menulis Siswa Kelas V SD Negeri 3 Puding Besar - Kamelia Husna; Maulina Hendrik; Silvio Juliana Nabela (JBES (Journal Basic Education Skills), 2024)
This research was motivated by the difficulty of students' writing skills. The difficulties experienced by students are: difficulties in spelling and punctuation; writing capital letters and words that are not quite correct; and a neatness of writing that is not assessed by aspects of the writing skills assessment. This research aims to determine the effect of the two-stay, two-stray model using a fishbone diagram on the writing skills of class V at SD Negeri 3 Puding Besar. This study employed quantitative research methods. The design used in this research was experimental. The design used in this study was pre-experimental in the form of a one-group pretest-posttest design. The sampling technique used in this study was saturated sampling. Data collection techniques in this study are tests, namely pretest-posttest. A paired sample t-test was the data analysis technique. The research findings indicated that the hypothesis testing yielded a t-count of 7867, which was higher than the t-table of 2,045. It showed that H0 was rejected and Ha was accepted, which meant an influence of the two-stay-two-stray model using fishbone diagrams on the writing skills of class V students at SD Negeri 3 Puding Besar.